Da universidade necessária à universidade para além do capital - Novaes, Henrique Tahan (Editora Oficina Universitária, 2022)
The debate on the role of the public university in Latin America "parked" on necessary but insufficient issues, such as: democratization of access, more funds for the expansion of the public system, better working conditions and student permanence. At the same time - in the context of the advance of the extreme right - barricades were erected against the system's budgetary asphyxiation, against the intervention of an authoritarian government in the elections, for the autonomy of the public university and freedom of thought. This Pocket Book brings to the debate another fundamental question: the meaning of the public university. As much as the public system grows or we have better working conditions, the teaching, research and extension agenda continues to be liberal, that is, aimed at meeting the needs of the job market or to meet an imitative standard of science, in general. based on productivism, innovation, alienated research and teaching, and welfare extension. A radical change in the meaning of the university in a dependent and neocolonial country like Brazil could place the university agenda in a finer tune with the struggles of organized social movements and - with that - contribute to the formation of a society beyond capital.